New Frontiers in Gut Nutrient Sensor Research: Prophylactic Effect of Glutamine Against Helicobacter pylori-Induced Gastric Diseases in Mongolian Gerbils - Kikuko Amagase; Eiji Nakamura; Takuya Endo; Shusaku Hayashi; Mai Hasumura; Hisayuki Uneyama; Kunio Torii; Koji Takeuchi (Elsevier, 2010)
Ammonia is one of the important toxins produced by Helicobacter pylori (H. pylori), the major cause of peptic ulcer diseases. We examined whether glutamine or marzulene (a gastroprotective drug containing 1% sodium azulene and 99% glutamine) protects the gastric mucosa against H. pylori in vivo and investigated the mechanism underlying glutamine-induced mucosal protection against ammonia in gastric epithelial cells in vitro. Mongolian gerbils were fed for 3 months with a diet containing glutamine (2% - 20%) or marzulene (20%) starting from 2 weeks or 2 years after H. pylori infection. Then, gastric mucosal changes were evaluated both macro- and microscopically. Cultured gastric epithelial cells were incubated in the presence of ammonia, with or without glutamine; and cell viability, ammonia accumulation, and chemokine production were determined. Gerbils exhibited edema, congestion, and erosion after 3-month infection; and after 2-year infection, they showed cancer-like changes in the gastric mucosa. Glutamine and marzulene significantly suppressed these pathological changes caused in the gastric mucosa by H. pylori infection. Ammonia was accumulated in the cells, resulting in an increase in chemokine production and a decrease in cell viability. These pathological responses were prevented by glutamine. In addition, glutamine decreased chemokine production and cell death through inhibition of cellular accumulation of ammonia, resulting in the prevention of H. pylori-induced gastric diseases in vivo. These results suggest that glutamine/marzulene would be useful for prophylactic treatment of H. pylori-induced gastric diseases in patients. Keywords:: glutamine, gastric mucosa, Helicobacter pylori, protection, cell death, gastrointestinal tract